UTILIZING PLASTIC BOTTLE WASTE WITH THE RE-USE METHOD - Yeti SUKARSIH; Sunu Dwi ANTORO; TRIYONO TRIYONO; Siti ZUHRIYAH; Kus Anjar S SISWATI (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2019)
This public service program aims to improve the creativity of the community through the re-use of household waste. Not only exciting, this activity may also generate extra income for the community members. The method consists of understanding the issues of environmental health, identifying and determining inorganic waste, and improving creativity through workshops on utilizing inorganic waste to generate side income. The object of this program is the housewives at Dusun Mrisen, Sardonoharjo, Ngaklik, Sleman, Yogyakarta. The activity methods used in this program are lectures, demonstration, and practicum. This public service program is expected to contribute in the improvement of the community’s welfare